2018
DOI: 10.3389/fphys.2018.00880
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Acidification Reduced the Resistance of Crassostrea gigas to Vibrio splendidus Challenge: An Energy Metabolism Perspective

Abstract: Negative physiological impacts induced by exposure to acidified seawater might sensitize marine organisms to future environmental stressors, such as disease outbreak. The goal of this study was to evaluate if ocean acidification (OA) could reduce the resistance capability of the Pacific oyster (Crassostrea gigas) to Vibrio splendidus challenge from an energy metabolism perspective. In this study, the Pacific oyster was exposed to OA (pH 7.6) for 28 days and then challenged by V. splendidus for another 72 h. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 94 publications
(111 reference statements)
2
12
0
Order By: Relevance
“…Upregulation of cox3, hspa12a, and hspa12b is a key indicator of high metabolic demand and oxidative stress [ 70 ], and the lack of expression of genes coding for antioxidant enzymes suggests that larvae are unable to effectively handle the oxidative stress and high metabolic demand due to the inability to rapidly clear RE22 infection. This is consistent with the well-documented effect of bacterial infection on the transcriptomes of susceptible bivalve hosts [ 53 , 67 , 71 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 90%
“…Upregulation of cox3, hspa12a, and hspa12b is a key indicator of high metabolic demand and oxidative stress [ 70 ], and the lack of expression of genes coding for antioxidant enzymes suggests that larvae are unable to effectively handle the oxidative stress and high metabolic demand due to the inability to rapidly clear RE22 infection. This is consistent with the well-documented effect of bacterial infection on the transcriptomes of susceptible bivalve hosts [ 53 , 67 , 71 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 90%
“…macromolecules biosynthesis). At a general level, we also detected higher expression of genes related to the AMPK signalling pathway, consistent with related work in the brain of sh exposed to OA a well as in other marine species (Schunter et al 2018;Cao et al 2018). Extending from these ndings, and unexpectedly, we also discovered that D. labrax, upon intergenerational exposure to OA, up-regulated gene programs conferring elevated resistance to virus infection.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have shown that modest increases in dissolved CO 2 (<1200 μatm) have little effect on metabolic rates, whereas extremely high levels of dissolved CO 2 (>5000 μatm) could depress metabolic rates (Michaelidis et al, 2005; Beniash et al, 2010; Hendriks et al, 2010; Thomsen and Melzner, 2010; Zhao et al, 2017b). As shown by Cao et al (2018), Pacific oyster ( Crassostrea gigas ) modulates energy sources by inhibiting aerobic energy metabolism, stimulating anaerobic metabolism, and increasing glycolytic enzyme activity following exposure to a reduced pH value of 7.6 for 28 days. The clams (Ruditapes philippinarum ) were reported to be able to maintain/regulate their physiological status and biochemical performance under reduced pH (7.3) for 28 days (Velez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%